2009
DOI: 10.2202/2161-2412.1051
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Beliefs on Inclusion and Teaching Students with Disabilities: A Representation of Diverse Voices

Abstract: The purpose of this study was to analyze the beliefs of physical education teachers on teaching students with disabilities in inclusive classes. Participants were 29 physical education teachers from Ghana (Africa), Japan, the United States, and Puerto Rico. The research paradigm was qualitatively descriptive using a multisite interview design (Gay, 1996) situated in the theory of planned behavior (Ajzen, 1991). The primary data source was interviewing. Interview data were analyzed with constant comparative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In general, findings from these studies revealed that physical education teachers tend to hold more positive attitudes toward teaching students with mild disabilities compared with students with more severe disabilities (Hodge et al, 2009;Kowalski & Rizzo, 1996;Rizzo, 1984;Rizzo & Vispoel, 1992). Rizzo (1984), Rizzo and Vispoel (1992) and Hodge and Jansma (1999) found in-service physical educafion teachers held more positive attitudes toward teaching students with learning disabilities compared with those with physical or behavioral disabilities.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In general, findings from these studies revealed that physical education teachers tend to hold more positive attitudes toward teaching students with mild disabilities compared with students with more severe disabilities (Hodge et al, 2009;Kowalski & Rizzo, 1996;Rizzo, 1984;Rizzo & Vispoel, 1992). Rizzo (1984), Rizzo and Vispoel (1992) and Hodge and Jansma (1999) found in-service physical educafion teachers held more positive attitudes toward teaching students with learning disabilities compared with those with physical or behavioral disabilities.…”
mentioning
confidence: 85%
“…Teachers with more teaching experience (Rizzo & Vispoel, 1991 ) and greater perceived competence (Rizzo & Kirkendall, 1995) were found to have significantly more positive attitudes toward teaching students with disabilities. Furthermore, coursework in APE (Ammah & Hodge, 2005;Hodge et al, 2009;Rizzo & Vispoel, 1991) and on-campus field-based experiences (Hodge & Jansma, 1999) were found to favorably enhance teachers' attitudes toward students with disabilities.…”
mentioning
confidence: 97%
“…Zimmerman (2018) stated that teachers gain the satisfaction of being completely engaged in their profession when their identity development enables them to practice using their personal talents. Hodge et al (2009) found that they mostly assist students in succeeding out of a sense of accomplishment and satisfaction. Nevertheless, their opinions on how simple or difficult it is to teach students who have disabilities vary.…”
Section: Accomplishment (A)mentioning
confidence: 99%